2020
DOI: 10.1186/s13256-019-2336-9
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic congenital Morgagni hernia presenting as a chest pain: a case report

Abstract: Background: Morgagni hernia is a rare form of congenital diaphragmatic hernia with a prevalence of 2-3%. It occurs due to a defect on the anterior part of the diaphragm, which allows abdominal organs to penetrate into the thoracic cavity. This condition can be detected during fetal life by routine ultrasonography or late during adult life. Late diagnosis of this condition in adults is extremely rare. According to our literature search, only a few cases of symptomatic hernia in adults have been reported so far.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…Morgagni hernia is the rarest of all CDH, presenting mostly in childhood [4] , [5] . There are some reports documenting its presentation in adulthood [7] , [8] , [9] , [10] . The present case, a 53 years' female was diagnosed as having CDH after developing cardiovascular and respiratory symptoms repeatedly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morgagni hernia is the rarest of all CDH, presenting mostly in childhood [4] , [5] . There are some reports documenting its presentation in adulthood [7] , [8] , [9] , [10] . The present case, a 53 years' female was diagnosed as having CDH after developing cardiovascular and respiratory symptoms repeatedly.…”
Section: Discussionmentioning
confidence: 99%
“…There is no strong recommendation on the cutoff size of the hernia defect to advise use of mesh. Mesh can be considered in cases where there is marked tissue loss of the diaphragm and primary repair is not possible [10] , [18] . Although removal of sac has many advantages like reduction of tissue trauma, low risk of fluid collection and low recurrence, it is advised that the sac not be removed due to the feared complication of massive pneumo-mediastinum [19] , [20] .…”
Section: Discussionmentioning
confidence: 99%
“…[14][15]. Mohamed et al reported an adult with CMH who presented with chest pain due to suspected loop of bowel compressing the right side of the chest [17]. There is also death reported in adult due to cardiac compression and cardiac tamponade secondary to CMH [18].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to select the specific type of injury and the exclusion of concomitant injuries allows for an effective acute repair. Anterior diaphragmatic injuries are more amenable to a primary repair and the goal remains a tension free repair [8]. The majority of penetrating trauma injuries are anterior diaphragmatic injuries.…”
Section: Discussionmentioning
confidence: 99%